Деякі особливості планувальної структури пізньоархаїчних поселень Нижнього Побужжя - Буйських, А.В. (Археологія, 1990)
У статті розглянуто метричні особливості будівництва жител та планувальної структури пізньоархаїчних поселень Нижнього Побужжя. Зроблено висновок про їх етнічну належність грекам-колоністам. Статья посвящена проблеме использования данных метрологии при застройке позднеархаических поселений Нижнего Побужья. На примере поселения Чертоватое-7 делается вывод о том, что, несмотря на общую стихийность застройки отдельных жилищно-хозяйственных комплексов, имели место элементы регламентации, а в качестве единого планировочного модуля использовался метрический стандарт самосского происхождения. На этом основании подтверждается тезис о принадлежности земляночных структур Нижнего Побужья грекам-колонистам. A problem on the use of the metrology data when building late-arch aie settle menu of the Lower Bug territory is considered. Taking settlement Chertovatoe-7 as an example, a conclusion is made that despite tfie general spontaneity of building observed in some housing-farming complexes, there were regulation elements and a metric standard of the Samossian origin was used as a single planning module. Proceeding from this a thesis on belonging of earth-houses of the Lower Bug territory to Greeks-colonists has been confirmed.